ANALISIS PENYUSUNAN LAPORAN KEUANGAN RUMAH MAKAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL, DAN MENENGAH - Nur Aina; Arifuddin; Safaruddin (Jurusan Akuntansi, Universitas Halu Oleo, 2026)
This research was conducted at Mama Winda's restaurant, which is one of the MSMEs in Bombana Regency. This study aims to compile financial reports based on Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) at Mama Winda's restaurant. This research use desciptive qualitative approach. Meanwhile, the data collection methods used were interviews, documentation and literature study. The results of this study indicate that Mama Winda's restaurant has not prepared financial reports in accordance with SAK EMKM because the recording of financial reports is only in the form of recording purchase transactions such as purchases of raw materials, equipment, and equipment in its business activities. The obstacles faced so that SAK EMKM was not implemented in the preparation of financial reports were caused by two factors, namely internal factors and external factors.